Microstructure and Mechanical Properties of the As‐Cast AlLiCuMgZr Alloy with High Li Content and Different Cu/Mg Ratios. Issue 7 (6th May 2020) - Yu, Tianfu; Qian, Bingyu; Wu, Ruizhi; Sun, Jianfeng; Zhao, Hui
Abstract : The microstructures and mechanical properties of as‐cast AlLiCuMgZr alloys with high Li content and different Cu/Mg ratios are investigated. The results show that the tensile strength increases and the elongation almost keeps unchanged, with the decrease in Cu/Mg ratio. The tensile fracture exhibits typical intergranular fracture. The main phases of as‐cast alloys are α(Al), δ′(Al3 Li), and T2 (Al6 Li3 Cu). With the decrease in Cu/Mg ratio, the size of the δ′(Al3 Li) phase increases, and the amount of T2 (Al6 Li3 Cu) phase at the grain boundary decreases. Moreover, the fine S1 (Al2 MgLi) phase and S′(Al2 CuMg) phase are formed inside the grains near the grain boundaries. The improved properties are attributed to the solution strengthening and second‐phase strengthening of δ′(Al3 Li). Abstract : With the decrease in Cu/Mg ratio in the as‐cast alloy, the strength increases and the plasticity almost remains unchanged. The increase in Mg content promotes the increase in the size of the δ′(Al3 Li) phase, and the main strengthening mechanisms of the alloy are solution strengthening and second‐phase strengthening of δ′(Al3 Li) phase.